A Workshop Combining Simulation and Self-Directed Learning to Teach Medical Students About Pneumonia - David Wald; Bettina Buttaro (Association of American Medical Colleges, 2016)
Abstract Introduction Self-directed learning as a form of active learning is student centered rather than the faculty-centered model employed in traditional lectures or large-group teaching. In order to highlight the content taught during a microbiology course we developed a 2-hour workshop to help teach second-year medical students about pneumonia. Methods One week prior to session, the class is divided into groups of 30 and then further divided into groups of five, each of which is assigned one of six cases to review. The student then attend the session and perform a high-fidelity simulation matching the case they were assigned. After a debrief with a faculty facilitator each group is asked to diagnose their patient and present it to the other 25 learners. Results The workshop has received positive evaluations from our students and has been reported to achieve the learning objectives. Most second-year medical students (97.1%, n = 171) reported that the self-directed learning component and simulation complemented each other and enhanced the learning experience. Discussion Most students view working as a team as a positive experience and favor a student-facilitated session. Because of the success of this workshop, we have modified others to follow a similar format.